Children First, Offenders Second: The Centrality of Engagement in Positive Youth Justice. (9th October 2014) - Case, Stephen; Haines, Kevin
Abstract Contemporary European youth justice practice, notably in England and Wales, fosters retrospective, risk‐focused and reductionist views of children. Enforced, inequitable, prescriptive and adult‐led youth justice relationships adulterise children and responsibilise them fully for their offending behaviour, disengaging them from constructive youth justice interventions. This article sets out and evidences an alternative model of youth justice: Children First, Offenders Second (CFOS). The CFOS model offers a whole child, preventative and diversionary approach that normalises offending by children and promotes strengths and positive behaviour. The model is grounded in the principles of child‐friendly, child‐appropriate and legitimate practice as a means of engaging children with youth justice services and interventions. Evidence of how these key principles have been animated in local practice is provided and implications for engagement in the youth justice context are discussed.